Revisiting Synonymy in the Glorious Qur’an: A Semantic Analysis of Itmām and Ikmāl (إشكالية الترادف في القرآن الكريم: دراسة دلالية لكلمتي إكمال وإتمام نموذجًا) - Ahmad Farhan Rif'an Najib; Ahmad Inzimam Haq; Kiki Budiyanto; Haqiqi Haqiqi (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose This study aimed to investigate the semantic distinction between the Qur’ānic terms Itmām and Ikmāl, often perceived as synonymous in Arabic linguistics, to clarify their precise meanings and implications for Qur’ānic interpretation. Method The research employed qualitative design using a semantic-linguistic approach with descriptive-analytical methods. Data were collected through library research, classical Qur’ānic exegesis, and linguistic sources. Selected verses containing Itmām and Ikmāl were analyzed to identify their contextual meanings. Results/findings The findings reveal that Itmām is generally associated with fulfilling obligations or bringing something to full completion in a continuous manner, whereas Ikmāl refers to the process of perfecting or completing something already initiated until it reaches its intended purpose. Conclusion The study concludes that understanding the distinction between Itmām and Ikmāl enriches Qur’ānic exegesis, enhances semantic studies in Arabic, and contributes to precise interpretation. It recommends further exploration of other synonym pairs in the Qur’an to broaden semantic research